2019
DOI: 10.1021/acs.est.9b02591
|View full text |Cite
|
Sign up to set email alerts
|

Organic Peroxides and Sulfur Dioxide in Aerosol: Source of Particulate Sulfate

Abstract: Sulfur oxides (SO x ) are important atmospheric trace species in both gas and particulate phases, and sulfate is a major component of atmospheric aerosol. One potentially important source of particulate sulfate formation is the oxidation of dissolved SO2 by organic peroxides, which comprises a major fraction of secondary organic aerosol (SOA). In this study, we investigated the reaction kinetics and mechanisms between SO2 and condensed-phase peroxides. pH-dependent aqueous phase reaction rate constants between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(121 citation statements)
references
References 79 publications
5
106
1
Order By: Relevance
“…As well, the importance of general acid catalysis needs to be considered not only for the many organic acids that are present under pollution conditions but potentially also for ammonium ions which are present in aerosol particles at very high concentrations. While such rate enhancements may arise under any conditions with a high aerosol liquid water content and solute concentrations, for the specific Chinese haze situation it is particularly important to assess these effects on the reactions of organic hydroperoxides, NO 2 and O 3 that also oxidize dissolved SO 2 (41), over a range of aerosol pH. This will permit a more comprehensive assessment of the overall rate of multiphase sulfur oxidation under cloud-free conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As well, the importance of general acid catalysis needs to be considered not only for the many organic acids that are present under pollution conditions but potentially also for ammonium ions which are present in aerosol particles at very high concentrations. While such rate enhancements may arise under any conditions with a high aerosol liquid water content and solute concentrations, for the specific Chinese haze situation it is particularly important to assess these effects on the reactions of organic hydroperoxides, NO 2 and O 3 that also oxidize dissolved SO 2 (41), over a range of aerosol pH. This will permit a more comprehensive assessment of the overall rate of multiphase sulfur oxidation under cloud-free conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have revealed the formation of OSs from photooxidation of anthropogenic precursors, such as polycyclic aromatic hydrocarbons (Riva et al, 2015) or long‐chain alkanes (Riva, Barbosa, et al, 2016), on sulfate seed particles. Moreover, direct formation of OSs from uptake of gaseous SO 2 by unsaturated fatty acids (Passananti et al, 2016; Shang et al, 2016) and organic peroxides (Wang, Zhou, et al, 2019) and OS formation from reaction of hydrogen sulfite with unsaturated carbonyl compounds in the presence of Fe 3+ (Huang, Cochran, et al, 2018) have been reported. However, the atmospheric relevance of these processes has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the uptake rate was instead estimated by measuring the sulfate production rate using AMS. However, it should also be noted that the sulfate collection and ionization efficiencies of AMS are highly uncertain, since the yield of organosulfate is significant from these reactions (Wang et al, 2019), and AMS has a lower sensitivity towards organosulfates especially under humid conditions in the current study as indicated by ion chromatography and SMPS measurements ( Fig.S10-12) (Chen et al, 2019;Farmer et al, 2010).…”
mentioning
confidence: 82%